NURSING SHORTAGE: EXPLORING THE PERCEPTION OF UNIMAS NURSING STUDENTS TOWARD NURSING SHORTAGE AND ITS IMPACT ON QUALITY OF CARE - BROOKLYN MAYANG, GUAN (Universiti Malaysia Sarawak, (UNIMAS), 2024)
Introduction: This study delves into the perception of UNIMAS nursing students regarding the critical issue of nursing shortage and its repercussions on the quality of care. The global shortage of nurses has emerged as a critical concern, affecting healthcare systems worldwide. In Malaysia, where the demand for healthcare services continues to rise alongside an aging population and increasing healthcare needs, understanding how nursing students perceive and anticipate the impact of this shortage is paramount. Aim: This study intended to explore the perception of nursing students towards nursing shortage and its impact on quality care and challenges faced by nursing students in clinical amidst nursing shortage. Methodology: Utilizing qualitative research methods, this study employs an in-depth interview with seven nursing students at UNIMAS to explore the nuanced perspectives of nursing students towards nursing and its impact on quality of care. An individual semi-structured interview question was used to collect data that aims to uncover insights on the contributing factors leading to shortages and the challenges faced by nursing students amidst nursing shortages. The collected data were transcribed and analyzed by using thematic analysis process. Findings: Nursing students highlighted nursing shortages as alarming issues, identifying three main themes: (1) Perception of nursing students on factors causing nursing shortage, (2) Impact on Quality of Care, and (3) Student Challenges Amid Shortages. They cited low wages, toxic work environments, and lack of professional recognition as key factors contributing to shortages, leading to compromised patient care and safety. Students also reported challenges amid shortages including lack of supervision, increased stress, and greater responsibilities. iv Conclusion: Low wages, toxic working environments and lack of professional recognition are the primary causes of nursing shortages in Malaysia. These issues deter individuals from pursuing nursing, compromise the quality of care, and increase stress among existing hospital staff. Addressing these challenges is crucial to improving the nursing workforce and ensuring better patient safety and outcomes.